Performance Evaluation Test of Low-Pressure Economizer and Corrected Calculation Method of Energy Saving Effect - Xuedong WANG; Mingchao JIANG; Ang SONG (发电技术)
The low-pressure economizer installed in the tail flue of coal burning boiler can reduce temperature of boiler discharge smoke, thus saving energy and reducing consumption. There are many factors affecting the energy saving effect of low-pressure economizer, which makes the performance evaluation and analysis uncertain. Performance evaluation test of energy saving effect of low-pressure economizer was carried out on a 220 MW unit. Under 4 electrical loads, a total of 24 conditions were tested with different operating modes and operating parameters of the low-pressure economizer. Using thermal performance test method, and the fitted curve of steam turbine main steam flow with energy saving effect, the energy saving effect of low-pressure economizer had been calculated. Under main steam flow corresponding to 4 electrical loads, the energy saving effect was 116.8, 96.7, 108.2 and 99.1kJ/(kW·h), respectively. By changing operating parameters of the low-pressure economizer, variation range of energy saving effect under different electric load conditions was obtained. According to heat balance equation and heat transfer equation, design heat transfer amount and actual heat exchange amount of the low-pressure economizer were calculated. The impact of operating parameters of low-pressure economizer on energy saving was calculated by using the equivalent enthalpy drop method. Under 220MW test condition, the test value of energy saving effect was 116.8kJ/(kW·h), and was 190.97kJ/(kW·h) after parameter being modified.